GreenerAge: Empowering Sustainable Transitions through Adult Education for 55+ people - Ines, Saavedra; Carina, Dantas; Joana, Vieira; Flávia, Rodrigues; Raúl, Castano-Rosa; Outi, Valkama; Pauliina, Baltzar; Sofie, Pelsmakers; Willeke, van Staalduinen; Karin, Stiehr; Lucia, Thielman; Bart, Borsje; et al. (Magyar Gerontológia, 2023)
The ageing of the global population is fast-moving. In Europe, the projections are that individuals aged 55 and older rise from approximately 35% in 2022 to around 40% of the total population by 2050 (Eurostat, 2020). Climate and sustainable actions should consider their participation and engagement. With accumulated life experiences, maturity, time, and knowledge, older adults can play a pivotal role in advancing a greener future, both at the individual and community levels.